Alleviating Society’s Economic Crisis: Narrative Policy on Social Safety Nets Policy Process During Covid-19 Pandemic - Alih Aji Nugroho; Ilima Fitri Azmi (Policy & Governance Review, 2021)
This study aimed to see how the coalition policy at the national level narrated the social safety net (JPS) policy as an effort to save people from the crisis during the Covid-19 Pandemic. Narrative Policy Framework (NPF) was used to analyze the influence of the policy narrative component from experts, executives, and their supporters on the JPS policy process. The method of the study was descriptive qualitative. The result of the study showed that the strategy of policy coalitions at the meso level in policy narrative influenced the social safety net policy-setting process. In the JPS policy narrative, groups supporting the policy fall into the category of status quo group which positioned itself as a hero. This group came from government circles who claimed that the JPS policy is for the benefit of the community. The second group (victims) came from people who believed in the notion that the implementation of JPS policies was problematic and inappropriate. Villain from the JPS narrative was characterized from a group that took advantage of the situation for personal gain. Moral of the story from JPS policy was that the hero tried to lead the narrative so that the story built legitimized the policy.